Growth Differentiation Factor-15 (GDF-15) as a Predictor of Major Adverse Cardiac Event in Acute Myocardial Infarction Patients - Annisa Tridamayanti; Trisulo Wasyanto; Ahmad Yasa’ (Acta Medica Indonesiana)
Background: Growth Differentiation Factor-15 (GDF-15) has emerged as a biomarker that capable to predicting cardiovascular events. Recent studies suggest that GDF-15 is elevated in patients with acute myocardial infarction (AMI), but the prognostic remains incompletely defined. This study aimed to investigate the role  of GDF-15 levels with major cardiac adverse events (MACE) on three months follow up in patients with AMI. Methods: This cohort study was conducted from November 2020 until May 2021 at Dr. Moewardi Hospital. GDF-15 was measured at admission, clinical data was collected and 3 months follow up events was registered. Prognostic value of GDF-15 and hazard ratio between high and low GDF-15 level were analyzed. Results: A total of 64 AMI patients were included in this study. MACE at three months follow-up occurred in 26.5% of patients. In multivariate analysis, GDF-15 was independently associated with risk of MACE at 3 months follow up (OR 1.501; p = 0.003). The cut-off point value of GDF-15 was analyzed with the ROC curve, obtained 2256 pg/mL which has a sensitivity of 94.1% and a specificity of 73.8% (area under the curve (AUC) 86.2%; 95% CI 0.768-0.956). Risk model with Kapplan Meier showed significant association between high GDF-15 levels (≥ 2256 pg/mL) and the incidence of MACE at 3 months follow up (HR 12.029; 95% CI 3.429- 42.197; p <0.001) Conclusion: In patients with AMI, high level of GDF-15 was significantly associated with the risk of MACE at 3 months of observation.